Cheap Talk with Correlated Signals - A. K. S. Chand; Sergio Currarini; Giovanni Ursino (Fondazione Eni Enrico Mattei (FEEM), 2013)
We consider a game of information transmission, with one informed decision maker gathering information from one or more informed senders. Private information is (conditionally) correlated across players, and communication is cheap talk. For the one sender case, we show that correlation unambiguously tightens the existence conditions for a truth-telling equilibrium. We then generalize the model to an arbitrary number of senders, and we find that, in this case, the effect of correlation on the incentives to report information truthfully is non monotone, and correlation may discipline senders' equilibrium behavior, making it easier to sustain truth-telling.
Keywords: C72; D82; D83; 330; Cheap Talk; Multiple Senders; Correlation